If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 8y = -15 Solving -5x + 8y = -15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. -5x + 8y + -8y = -15 + -8y Combine like terms: 8y + -8y = 0 -5x + 0 = -15 + -8y -5x = -15 + -8y Divide each side by '-5'. x = 3 + 1.6y Simplifying x = 3 + 1.6y
| h-5=17 | | n+5=44 | | n+8=43 | | 5(2x+5)-2(3x-4)= | | 2y(y^2+3)= | | 11x+5y=-2 | | -25=6a-15-15a | | 3x+2=-y | | (X/4)5= | | 13x-8=39 | | 98x-199y=1 | | X-10y=-94 | | 3/20=1/4× | | 3y-4(10y-94)=6 | | m^3+5=0 | | (2/5)x=4/25 | | -4/9.5/8 | | 0.3x=20 | | 2x-(2x+5)=0 | | 2n^2+18n=580*2 | | 3=13+K | | A-2=2-A | | 18n/2 | | -3-5=-2+5 | | -24=-6+n | | 4+4(6-1)= | | -4-5x=-8+x | | -7(x+3)-17=16+2 | | Y-2x^2-x+10=0 | | (1-x)(1-2x)(1+3x)=36 | | n=840 | | Y/-6=3 |